Odpowiedzi

2009-12-06T19:44:41+01:00
6x-9y=21
-6x+10y=-22

y=-1

-6x-10=-22
-6x=-12
x=2

y=1
x=-2
5 4 5
2009-12-06T19:45:49+01:00
2x-3y=7 | * (-3)
3x-5y=11 | * 2

-6x + 9y = -21
6x - 10y = 22

sumujemy:

9y - 10y = -21 + 22
-y = 1 | * (-1)
y = -1

podstawiamy do pierwszego równania:
2x - 3 * (-1) = 7
2x + 3 = 7
2x = 4 | /2
x = 2

czyli
x = 2
y = -1
4 5 4
Najlepsza Odpowiedź!
2009-12-06T19:46:08+01:00
Metodą przeciwnych współczynników
2x-3y=7/*(-3)
3x-5y=11/*2

-6x+9y=-21
6x-10y=22
------------------
-y=1
y=-1

2x-3y=7
y=-1

2x-3(-1)=7
y=-1

2x=7-3
y=-1

x=2
y=-1
3 5 3